Adolescent women's perspectives of homelessness in the Canadian north. - Le Camp, Janet (Author); Tang, Kwong-leung (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2006)
No abstract available. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1302342